Geothermal favourability mapping by advanced geospatial overlay analysis: Tuscany case study (Italy). (October 2015) - Procesi, M.; Buttinelli, M.; Pignone, M.
Abstract: The geothermal resource exploration generally requires a combined analysis of various geo-information datasets. In this framework the geospatial analysis as the weighted overlay, performed under GIS (Geographic Information Systems) environment, represent a strong tool to solve problems such as the site selection. This technique is applied on not homogeneous input data to perform an integrated analysis and producing favourability maps. This work is based on the development of a new weighted overlay scheme, that combines favourable geological factors, which allow the identification of hydrothermal geothermal resources, and geological hazards (seismicity and volcanism), which can potentially limit the exploitation of a geothermal resource. The technique was tested on Tuscany Region (Italy), where two geothermal fields, Larderello-Travale/Radicondoli and Monte Amiata, are in operation. Results show that the most promising areas mostly coincide with the exploited geothermal fields. Moreover, new areas with a high geothermal favourability are identified. Low-cost and rapid resource evaluation approaches like this could play a key role during the early stages of a geothermal exploration plan. Moreover, this methodology could be extensively used in other geothermal areas not only by the scientific community but also by stakeholders, as first concrete tool to explore a potential resource suitable for exploitation. Highlights: GIS techniques to recognize potential areas suitable for geothermal exploitation. The weighted overlay is a powerful tool in the first phase of an exploration program. The proposed methodology could be used by both scientific community and stakeholders.